2013
DOI: 10.3390/ph6040536
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Studies on Novel N-Substituted Bicyclo-Heptan-2-Amines at NMDA Receptors

Abstract: Several novel norcamphor derivatives were designed and synthesized as uncompetitive NMDA receptor antagonists at the phencyclidine (PCP) binding site. Such compounds have potential as ligands for understanding and possibly the treatment of several neurodegenerative disorders and other glutamate-dependent disorders. We examined the toxic effects of the compounds as compared with memantine, an NMDA receptor antagonist that is FDA approved for treatment of Alzheimer’s disease, by testing these compounds on two ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…It has been reported that memantine at doses above 100 μM is toxic to the neuronal cell line N2A and kidney cell line MDCK . We did not observe any effect of memantine alone on cell viability or apoptosis.…”
Section: Discussioncontrasting
confidence: 73%
“…It has been reported that memantine at doses above 100 μM is toxic to the neuronal cell line N2A and kidney cell line MDCK . We did not observe any effect of memantine alone on cell viability or apoptosis.…”
Section: Discussioncontrasting
confidence: 73%
“…On the contrary, in the present investigation, the application of 100 mM of SLNs-MEM induced a slight citotoxicity leading to a reduction of cell viability likely related to oxidative alterations in N2a NB and PHWB cells. Similar to these findings, MEM applications at 100 mM led to notable decreases of cell viability in both N2a NB and MDCK cell lines, as determined by MTT assay during 24 h (Coleman et al, 2013). Again, the determined TAC and TOS levels were similar in 100 mM SLNs-LA-MEM treated and untreated cultures while SLNs-MEM treatments altered the oxidative status.…”
Section: Citotoxicity Studies Of Slns-la-memsupporting
confidence: 77%
“…This method allows for measuring the total heat flow of material, as well as its nonreversible and reversible heat capacities. A detailed description of the MDSC method can be found elsewhere [50][51][52][53][54][55][56][57]. MDSC experiments were performed using a Model Q200 from TA Instruments, USA.…”
Section: Modulated Differential Scanning Calorimetry (Mdsc)mentioning
confidence: 99%
“…Prior to all measurements, temperature calibration was done with a sapphire disc, under the same experimental conditions used for all 9OO4/CNT samples. The analysis method used to extract the complex specific heat is based on linear response theory [50,58]. In general, a temperature oscillation is described as T(t) = T 0 + T˙0 t + A T sin(ωt), where T 0 is the initial temperature at time t = 0, T indicates the absolute temperature at time t, T˙0 represents the baseline temperature scan rate, A T is the temperature amplitude, and ω (ω = 2πf) is the angular frequency of the temperature modulation.…”
Section: Modulated Differential Scanning Calorimetry (Mdsc)mentioning
confidence: 99%